Form and function of someTheban resonances in Homer’s Iliad and Odyssey - Vergados, Athanassios (De Gruyter, 2018)
The aim of this paper is to explore the different ways in which the Iliad and the Odyssey incorporate material from the Theban traditions into their own narrative fabric. First, I examine the references to Tydeus in the Iliad , addressing the function these references acquire each time they appear in a character’s speech. In a second step I turn my attention to the allusions to Theban stories in the Odyssey , and in the Nekyia in particular. In this case too I will be zeroing in on the function of the Theban reminiscences. It will be shown that whereas the Theban reflections in the Iliad occur in a linear manner, the Odyssey incorporates the Theban material in a more intricate way. Finally, I will offer an explanation for the two poems’ difference in their interaction with the corpus of Theban stories: the Iliad in general chooses material that conforms to the poem’s preoccupation with the heroes’ relative worth compared to earlier generations. In the Odyssey, on the other hand, the Theban material is combined with allusions to other local sagas, all of which it incorporates in order to supersede them and present itself as the “newest song.”
Aus: Trends in Classics, 6 (30 October 2014), Nr. 2. pp. 437-451. ISSN 1866-7481